2008
DOI: 10.1002/ajmg.b.30786
|View full text |Cite
|
Sign up to set email alerts
|

Mood and anxiety disorders in females with the FMR1 premutation

Abstract: Fragile X syndrome (FXS) is a model for studying the relative contributions of genetic and environmental factors to psychiatric disorders in mothers of children with disabilities. Here, we examine the frequency and predictors of mood and anxiety disorders in mothers with the FMR1 premutation. Ninety-three females with the FMR1 premutation were in the study and were compared to 2,159 women from the National Comorbidity Survey Replication (NCS-R) dataset. Mood and anxiety disorders were assessed using the SCID-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
301
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(328 citation statements)
references
References 31 publications
22
301
4
1
Order By: Relevance
“…Regarding anxiety disorders, Roberts et al (2009) [49] found that overall, these women displayed a lower frequency of anxiety disorders, although as mentioned before, specific entities such as lifetime panic disorder without agoraphobia and agoraphobia without panic at the time of the study were more likely among carriers. This lower frequency of anxiety disorders goes against previous findings by other groups who have found that women carriers tend to have an increased risk of anxiety disorders; in fact, Franke et al (1998) [47] reported a 41% lifetime diagnosis rate of anxiety disorder among carriers with FXS children.…”
Section: Neuropsychiatric and Muscular Involvementmentioning
confidence: 58%
See 4 more Smart Citations
“…Regarding anxiety disorders, Roberts et al (2009) [49] found that overall, these women displayed a lower frequency of anxiety disorders, although as mentioned before, specific entities such as lifetime panic disorder without agoraphobia and agoraphobia without panic at the time of the study were more likely among carriers. This lower frequency of anxiety disorders goes against previous findings by other groups who have found that women carriers tend to have an increased risk of anxiety disorders; in fact, Franke et al (1998) [47] reported a 41% lifetime diagnosis rate of anxiety disorder among carriers with FXS children.…”
Section: Neuropsychiatric and Muscular Involvementmentioning
confidence: 58%
“…Unlike the findings of Roberts et al (2009) [49], Obadia et al (2013) [50], when evaluating the characteristics of postpartum depression (PPD) during a pilot study done in carriers, found that mothers of children with FXS are at higher risk for PPD than female carriers without affected children and that for each additional child with FXS, the risk more than doubled. PPD episodes in this study were linked to having children with FXS since all PPD episodes occurred after carriers had a child who was eventually diagnosed with FXS, even though the syndrome's diagnosis was usually done years later.…”
Section: Neuropsychiatric and Muscular Involvementmentioning
confidence: 82%
See 3 more Smart Citations